Campo e cidade : um estudo das relações texto-imagem em Cesário Verde e em Camille Pissarro - Marinotti, Célia Soares (2012)
The Portuguese poet Joaquim José Cesário Verde (1855-1886) was an artist who showed his historical moment through his poetry, a rich sensitivity that can be studied from a decadent Romanticism to Realism ironic one, joining a note of pessimism arising out of your skepticism. His work also involves morbidity of Naturalism, presenting characteristics of Impressionism and anticipation of Surrealism. His poetry takes many forms and shades, features that include among the Parnassian, the Symbolists and the precursors of Modernism, factors that prevent classify his poetry to a single categorization. The poetry practiced by Cesário Verde takes the reader to take on the actually a more free and unimpeded, able to understand it in its novelty, the resulting interest in the everyday not limited to the city, but the reality facing country, which shares land with a civilization. The theme of the countryside and the city is on the proposal for an obvious trail to the camp, looking beyond a healthy life, strength to live. The work of Cesário Verde has been studied in the aspects of the real poeticization; the dichotomy town / country, the presence of women, the importance of representation of everyday life in the poetry of Cesário Verde, highlighting its language and style. Our proposal, however, seeks to identify the relationship between rural-urban, establishing a parallel with the Impressionist aesthetic, literary correspondent of "live painting" advocated by Manet, Degas, among others. Among the highlight Impressionist Camille Pissarro (1830-1903), French artist considered the "painter of the earth," which describes throughout his career, plowed fields and countryside, sleepy villages and bustling cities too, identifying with the proposal poetic of Cesário Verde. The research is anchored in the theoretical assumptions of comparative literature, gender and lyrical reading of the image. We discussed the ideas of Carvalhal, Coutinho and Nitrini; Aguiar e Silva, Bosi and Judice, Jolly and Rufach, Pena and Toá. The results were obtained from the Comparative Literature with the poetic work of Cesário Verde and Camille Pissarro's canvases which confirm the possibility of reading.